Faktor-Faktor yang Berhubungan dengan Kepatuhan Perawat dalam Melakukan Hand Hygiene di Ruang Rawat Inap RSI Siti Rahmah Padang - Nopan Saputra; Yance Komela Sari; Anggra Trisna Ajani; Tedy Asharyadi (Universitas Batanghari Jambi, 2023)
The purpose of this study was to determine the factors related to nurse compliance in performing hand hygiene in the Inpatient Room of RSI Siti Rahmah Padang. This type of research is an analytic survey with a research design using a cross sectional study. The research instrument used observation sheets and questionnaires. Data analysis techniques in this study were univariate and bivariate data analysis. The results of the study found that there was a relationship between motivation, facilities, supervision and the level of nurse compliance in performing hand hygiene in the inpatient room of RSI Siti Rahmah Padang.